Penyelesaian Sengketa melalui Pendekatan Adat - Abdurrahman Abdurrahman (Universitas Syiah Kuala, 2010)
ABSTRACT: There are available some alternative dispute settlement method in the community life, it is commonly through formal way (litigation) and also can be used through informal way (non litigation). One of informal dispute settlement is through customary approach which is undertaken by adat institution. The dispute settlement through adat approach has the main purpose that is to keep harmonisation and relationship among the community, not only providing the legal certainty but also the justice. In the life of Aceh’ people, the customary dispute settlement was done by adat institution at Gampong (village) and Mukim level. And for this, it has been promulgated already under several Qanun (regional law) of Aceh. The application of customary dispute settlement in Aceh is supported by any general principles that can provide protection for the rights of disputed parties. Dispute Stelement Through Customary Approach